A strategy for regulatory action when new adverse effects of a licensed product emerge. - Aronson, J; Price, D; Ferner, R (2009)
Regulatory agencies grant product licences (marketing authorizations) for medicinal products in the light of evidence that the balance between benefit and harm in the population is favourable. Here we consider a framework for allowing regulatory agencies to make rational decisions when reviewing product licences in the light of new information about harms that change that balance. The regulator can revoke the product licence, restrict the product's availability or change the 'label' in different ways. We examine the features of the adverse effect that may be relevant in making the decision: namely, individual differences in susceptibility; the possibility of monitoring; and the availability of protective strategies. The balance of benefit and harm, and the time-course and dose relation of the adverse effect play important roles in the decision-making process. We set out how these factors can help determine the logical response to new information on the balance between benefit and harm, and provide a series of relevant examples. We believe that when regulatory agencies have to decide how to amend the product licence of a drug when new serious adverse effects cause concern, they would find it useful to adopt a framework of this kind, using different strategies for different cases. Our proposed framework could also be useful in risk management planning during drug development.